1984
DOI: 10.1152/jappl.1984.56.3.607
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transcendental meditation on breathing and respiratory control

Abstract: We studied the effect of transcendental meditation (TM) on breathing using 16 experienced meditators and 16 control subjects. In controls, there was no significant difference in minute ventilation (VE), respiratory pattern, or hypercapnic response, whether breathing with eyes open-awake (CA), or with eyes closed-relaxing (CR). In meditators, VE decreased significantly during quiet breathing from 14.0 +/- 0.7 1/min with eyes open-awake (MA) to 12.4 +/- 0.6 1/min during meditation (MM) (P less than 0.02). The ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…As it can be observed in Table 1, the data in the present study corroborate the ones found in literature as they emphasize the occurrence of a hypometabolic state during meditation (Wallace 1970;Wolkove et al 1984;Young and Taylor 1998;Dusek et al 2005;Jevning et al 1992). However, since we aimed at assessing the cardiorespiratory and metabolic changes that took place during the same yoga session, we chose to reproduce the sequence of exercises proposed for one traditional hatha-yoga class (pranayamas followed by meditation).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As it can be observed in Table 1, the data in the present study corroborate the ones found in literature as they emphasize the occurrence of a hypometabolic state during meditation (Wallace 1970;Wolkove et al 1984;Young and Taylor 1998;Dusek et al 2005;Jevning et al 1992). However, since we aimed at assessing the cardiorespiratory and metabolic changes that took place during the same yoga session, we chose to reproduce the sequence of exercises proposed for one traditional hatha-yoga class (pranayamas followed by meditation).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, the control group presented a greater chemosensitivity to respiratory stimuli generated by hypercapnia (Wolkove et al 1984).…”
Section: Introductionmentioning
confidence: 75%
“…Regulated deep breathing with an emphasis on slow controlled expiration plays a role in yoga exercises. Depending on whether the yoga or meditation emphasizes relaxation or deep breathing exercises, the metabolic rate and respiratory frequency may go down, and the sensitivity to inhaled CO 2 may decrease (294). On the other hand, breathing exercises may represent a significant increase in metabolic demand, and in this setting oxygen consumption may actually increase even when the breathing occurs in the context of a meditative and relaxing regimen (269).…”
Section: Cognitive and Emotional Activities That Interact With Breathingmentioning
confidence: 99%
“…As attention to breathing is a common element in meditation training in many traditions [8], and as meditation is known to have lasting effects on respiration control [9] and respiration rate, skin conductance, and oxygen consumption are all reduced [10], it is plausible that the long-term practice of such forms of meditation might induce structural changes in brain regions involved in basic autonomic regulation as suggested earlier [8,11].…”
Section: Introductionmentioning
confidence: 99%